Physical demands of National Collegiate Athletic Association Division I football players during preseason training in the heat - DeMartini, J. K.; Martschinske, J. L.; Casa, D. J.; Lopez, R. M.; Ganio, M. S.; Walz, S. M.; Coris, E. E. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to evaluate physical demands of football players during preseason practices in the heat. Furthermore, we sought to compare how physical demands differ between positions and playing status. Male National Collegiate Athletic Association Division 1 football players (n = 49) participated in 9 practice sessions (142 ± 16 minutes per session; wet bulb globe temperature (WBGT) 28.75 ± 2.11°C) over 8 days. Heart rate (HR) and global positioning system data were recorded throughout the entirety of each practice to determine the distance covered (DC), velocity (V), maximal HR (HRmax), and average HR (HRavg). The subjects were divided into 2 groups: linemen (L) (N = 25; age: 22 ± 1 years, weight: 126 ± 16 kg, height: 190 ± 4 cm,) vs. nonlinemen (NL) (N = 24; age: 21 ± 1 years, weight: 91 ± 11 kg, height: 183 ± 8 cm) and starters (S) (N = 17; age: 21 ± 1 years, weight: 118 ± 21 kg, height: 190 ± 7 cm) vs. nonstarters (NS) (N = 32; age: 20 ± 1 years, weight: 105 ± 22 kg, height: 185 ± 7 cm) for statistical analysis. The DC (3,532 ± 943 vs. 2,573 ± 489 m; p = 0.001) and HRmax (201 ± 9 vs. 194 ± 11 b/min; p = 0.025) were significantly greater in NL compared with that in L. In addition, NL spent more time (p < 0.0001) and covered more distance (p = 0.002) at higher velocities than L did. Differences between S vs. NS were observed (p = 0.008, p = 0.031), with S obtaining higher velocities than NS did. Given the demands of their playing positions, NL were required to cover more distance at higher velocities, resulting in a greater HRmax than that of L. Therefore, it appears that L engage in more isometric work than NL do. In addition, the players exposed to similar practice demands provide similar work output during preseason practice sessions regardless of their playing status.